Cancer risk in patients with osteoporosis: a population-based cohort study. (3rd April 2017) - Sun, Li-Min; Liang, Ji-An; Lin, Cheng-Li; Lin, Ming-Chia; Chang, Nai-Jen; Kao, Chia-Hung
Abstract: Background: Osteoporosis has been associated with cancer development. We conducted a nationwide population-based cohort study in Taiwan to evaluate this possible association of osteoporosis with subsequent cancer development. Methods: A total of 35, 979 patients diagnosed with osteoporosis between 2000 and 2010 identified from the National Health Insurance Research Database comprised the osteoporosis cohort, and each patient was randomly frequency matched with one individual from the general population (without osteoporosis) based on age, sex, and year of osteoporosis diagnosis to form the non-osteoporosis (control) cohort. Cox proportional hazard regression analysis was used to calculate adjusted hazard ratios and 95% confidence intervals and determine the effect of osteoporosis on cancer risk. Results: Patients with osteoporosis showed a significantly higher risk of developing liver and thyroid cancers and lower risk of colorectal cancer than did individuals without osteoporosis. Male patients with osteoporosis had a significantly increased risk for liver cancer, whereas female patients with osteoporosis had a significantly increased risk for thyroid cancer, but a significantly decreased risk for overall and colorectal cancers. In addition, more significant findings were observed when age ≤64 years or the follow-up duration was ≤5 years; however, a significantly lower risk for colorectal cancer was observed when follow-up duration was >5 years. Study limits including lack of data for some health-related behaviors, inclusion criteria of osteoporosis and potential selection bias have been discussed. Conclusion: Patients with osteoporosis showed a higher risk for liver and thyroid cancers and a lower risk for colorectal cancer than did control individuals. Stratified analyses by sex, age, and follow-up duration showed various patterns in different cancers.